Representation Gaps in Digital Humanities: A Case Study of Marginalized Languages and Cultures in Indonesia - Jaizul, Alim; Lestari, Mugi (Communication in Research and Publications (CRP), 2025)
This study examines the gap in representation of marginal languages ​​and cultures in digital humanities in Indonesia. As a country with more than 700 regional languages, Indonesia faces serious challenges in preserving linguistic diversity in the digital era. Urbanization, globalization, and the dominance of the Indonesian language have accelerated the extinction of regional languages, with only 13 regional languages ​​having more than one million speakers. In the digital context, local languages ​​and cultures tend to be marginalized by the dominance of the majority and global languages. Through a qualitative approach and literature review, this study identifies several key issues: the inequality of local language representation in digital humanities projects, limited data and resources, and minimal participation of local communities. Several initiatives such as BASAbali and NusaWrites demonstrate good practices in preserving languages ​​through community-based approaches and the development of quality corpuses. However, structural challenges such as uneven digital infrastructure, low digital literacy, and the dominance of Western epistemology remain significant obstacles. This study recommends a collaborative approach between academics, local communities, government, and the private sector to build inclusive policies and initiatives. Digital technology needs to be positioned as a means of empowering local culture, not an instrument of global cultural domination, so that digital humanities can become a fair and representative space for the richness of Indonesian languages ​​and cultures.